Evaluation of pulmonary function, signs and symptoms of TMD and craniocervical dysfunction in individuals with chronic respiratory diseases (Research, Society and Development, 2022)
Objective: To relate the severity of signs and symptoms of TMD and cervical dysfunction with pulmonary function in individuals with chronic respiratory diseases. Methods: 13 individuals diagnosed with chronic respiratory diseases attended at the physiotherapy school clinic, EBSERH outpatient clinic and UFS students were included, nine females and four males, aged between 18 and 50 years. In the evaluation, the ProDTMmulti was used to quantify the frequency and severity of TMD signs and symptoms, the Craniocervical Dysfunction Index to assess cervical mobility, muscle pain, pain during movement, cervical spine dysfunction and analysis of posture and function tests. breathing with a ventilometer. Results and Discussion: A higher prevalence of absence of TMD signs and symptoms was found, except for neck pain (53.85%), feeling of plugged ear (53.85%) and tooth sensitivity (53.85%), in that the mild degree was more prevalent. All subjects presented cervical alterations, 69% with moderate dysfunction and 31% with severe dysfunction. And they showed no ventilatory changes. There was no significant correlation between chronic respiratory diseases and the degree of severity of TMD signs and symptoms and craniocervical dysfunction. Conclusion: There was no correlation between chronic respiratory diseases and pulmonary function with the presence of craniocervical dysfunction and TMD in the evaluated sample. However, it was possible to verify that part of these individuals presented signs and symptoms of TMD, such as cervical pain, sensation of plugged ears and sensitivity in the teeth, and that all of them presented craniocervical dysfunction of moderate to severe severity.